Kazık taşıma kapasitesinin statik formüllerle bulunması - Hergüner, Taner (Fen Bilimleri Enstitüsü, 1992)
Kazıklar en genel anlamıyla üzerindeki yapının yüklerini daha derinlerdeki taşıma gücü daha yüksek olan zemin veya kaya tabakasına aktarmak için kullanılan; ince, uzun yapı elamanlarıdır. Kazıklar ayrıca; şevlerin sağlamlaştırılmasında, kaldırma kuvvetlerinin ve yatay zemin itkilerinin karşılanmasında, limanlar ve köprü ayakları gibi su içinde yapılan yapılarda ve palplanş perde yapımında kullanılmaktadır. Kazık taşıma gücü hesap yöntemlerinin incelendiği bu çalışma sekiz ana bölümden oluşmaktadır. Birinci bölümde; çalışmanın amacı ve kapsamı verilmiştir. İkinci bölümde ; kazıklı temeller hakkında genel bilgiler verilmiş tir. Üçüncü bölümde ; kazık taşıma gücü hesabı için yapılması gerekli araştırmalar belirtilmiştir. Dördüncü bölümde; laboratuvar deneylerinden elde edilen veriler ile kazık taşıma gücü hesabı yapılmıştır. Beşinci bölümde ; arazi deneyleri yöntem verileri ile gerek kohezyonlu, gerekse kohezyonsuz zeminlerde kazık taşıma gücü hesabı yapılmıştır. Altıncı bölümde ; emniyetli kazık taşıma gücünün ^ulunması için yöntemler verilmiştir. Yedinci bölümde ; kazik taşıma gücüne zamanın etkisi incelenmiştir. Ekler bölümünde ; uygulamadan sayısal örnekler verilmiştir.

The purpose of the main function of piles is to transfer the load to lower levels in the ground, which are capable of sustaining the load with an adequate factor of safety and without setting at the working load by an amount detrimental to the structure that they support. The piles carry the loads mainly in axial compression but there are numereous examples where piles may be required to carry uplift loads when used to support tall structures subjected to overturning forces from winds or waves. Piles are also used in marine structures where they are subjected to lateral loads from the impact of berthing ships and from waves. The piles used to support retaining walls carry the combination of vertical and horizontal loads. Piles can be classified with respect to different criterions. They can be devided in terms of their function as; a. Friction (floating) piles, b. End-bearing piles, c. Compactions piles, d. Anchor piles. In order to categorize the various types of piles and their method of installation, a simple division into; a. Driven, b. Driven and cast in-situ, c. Bored, d. Screwed, piles is often employed. Some codes and researchers places piles in three categorious as follows; a. Large-displacement piles, b. Small-displacement piles, c. Non-displacement piles, Piles according to material used in their installation can be classified as; vi a. Timber piles, b. Concrete piles, c. steel piles. In the second chapter, different kinds of piles have been discussed, in addition to the factors of safety and economy, before choosing what kind of pile will be used in design, advantages and disadvantages of different kinds of piles should be used in design, advantages and disadvantages of different kinds of piles should be considered. The ultimate bearing capacity of a single pile can be evaluated from ; a. Static calculations, b. Field tests, c. Pile load tests, d. Pile driving formulas, e. The wave equation analysis. The accuracy of different calculation methods depends to a large extend on the reliability of the measurements of the strength and deformation properties of the soils and thus on the accuracy and the extend of the soil investigation. The ground investigation is paramount to the success of the piling works and needs to be carried out by competent and experinced persons. Borings, which need to be supplemented where appropriate by penetration tests, need to be taken on the site of the work, and they should go down to such depths as are adequate to explore the nature of the soil both around and beneath the proposed pile, particularly in those strata that are likely to contribute significantly to settlement. Undisturbed samples in cohesive soils are taken from borings and tested for strength so that compressibility and other characteristics to provide information on the carrying capacity of the soils at various depths can be established. It- is thus that are able to evaluate in the preliminary way the length and spacing of the piles. As a matter of course the standing of levels in the various strata and gradients between bore holes be noted. The investigation should take into account nearby structures by having a careful appraisal of their conditions, as the oventual choice of pile may well be determined by the effects which it is installation would have on such structures. A preliminary examination from records or trial holes of the nature of foundations of such buildings and should vii certainly note any evidence of past settlement, subsidence or slips. Every design will need to satisfy two conditions. Firstly, the factor of safety against failure both of the fabric of the foundation and in particular the differential settlement of the working load will have to be no more than the value that can be tolerated by the complete structure The first chapter of this thesis contains the purpose of the bearing capacity of piles. In chapter two; following subjects are examined: 1. Type of piles, 2. Comparison of piles, 3. Installation of piles, 4. Length of piles in the soil layers, 5. Determination of bearing capacitiy of piles. They consist of the main charactaristic of a pile and pile groups. And relates with soil behaviour. The basic measurements systems of determination of a pile's bearing capacity is in chapter three. They can be determined by these in-situ and laboratory tests. They are; a. Soil investigations, b. Laboratory tests, c. In-situ tests,. Standart penetrometer test (SPT). Ram soundings, tip A. Cone penetrometer test (CPT). Correlation between standart penetrometer test (SPT) and cone penetrometer test (CPT). Weight soundings. Pressuremeter test. In-situ vane test viii In three main division with the resuls oflaboratory tests, bearing capacity had been measured, in chapter 4. In this section bearing capacity and correlations are calculated for cohesive and non-cohesive soil. Laboratory measurements of in-situ soil parameters are at best unreliable and at worst misleading. This comes about, because of the difficulty of obtaining undisturbed samples and the problems of recreating in-situ conditions in the laboratory. Sample disturbance can seriously effect estimations of undrained shear strength and compressibility. Undisturbed samples of granular materials are near imposible to obtain so laboratory tests become meaningless unless being correlated with in-situ measurements. In chapter 5, calculations of the bearing capacity from field tests have been presented. Prior to correlations between the bearing capacity and the test results. The test techniques and the interpretation of the results in geotechnical engineering have been given as three main groups; a. Determination of bearing capacity of pile by standart penetrometer tests (SPT), b. Correlation between cone penetrometer test (CPT) and bearing capacity of pile, c. Correlation between Menard penetrometer test (MPT) and bearing capacity of pile, In non-cohesive soils, correlations have been developed for estimating end-bearing pressure directly from the results of standart penetration testing. Correlations of results from standart penetration tests, with the relative density > internal friction angle of the sand and effective overburden stress, may be used for this purpose. Results from standart penetration tests may also be used to provide an approximate guide to the shaft capacity of piles in cohesionless soils. Where cone penetration testing has been carried out, the end- bearing resistance for piles in cohesionless soils may be obtained directly from cone penetration test results. Modern cone penetration techniques, where a friction sleeve is used immediately behind the cone, enable the skin friction to be estimated directly for piles in non-cohesive soils. The cone penetration test has an important role in the exploration of cohesionless soils, because there is a lack of IX satisfactory alternative methods. Laboratory testing is generally not feasible, because of the difficulty of obtaining undisturbed samples. Cone penetration test results can also be corralated into equivalent standart penetration test " N " values in order to use correlations between " N " and engineering parameters and performance. Results from standart penetration or cone penetration tests in cohesive soils may be used to estimate the shear strength of the soil, and hence to provide estimates of end-bearing pressure and skin friction. The ultimate bearing capacity of friction piles in cohesionless soils can also be estimated from Ram Soundings. Test results indicate that the penetration resistance from Ram Soundings type A (blows/20cm) corresponds to the N-value (blows/30cm) penetration from standart penetrometer test. Therefore, the same calculation methods can be used for Ram Soundings Type A as for standart penetration tests. The bearing capacity of friction piles in sand can also be estimated from weight soundings. In every types of soil, pressuremeter test results can be used directly to predict the bearing capacity of piles without the added complication and expense of supplementary laboratory tests which may be required with traditional approaches. A number of changes has been made to pressuremeter technology over the years. Today, Menard Pressuremeter is used extensively to estimate the bearing capacity of piles. Results from Menard Pressuremeter Tests (MPT) can be used to evaluate base resistance and adhesion or friction on the sides of a pile. The most reliable means of determining the ultimate bearing capacity of a single pile is with pile load tests. Load testing of piles is expensive and the coast should be carefully weight against the reduction in risk and assurance of satisfactory behaviour that the pile test provides. For test procedures and the interpretations of the test results, there are different ideas suggested by some codes and researchers. Some measurement system of safe bearing capacity is the subject of the section six. The formulas, correlations and equations developed by scientists are examined and they are resulted according to; a. The formula of the optimum productivity of a pile, b. Terzaghi-Peck Method, c. Measurement system of the consolidation of a pile, They are basic and necessary factors for the pile calculation. In chapter 7, discussions of the axial capacity of piles has been completed with some comments on the effects of time. The design methods that have been described are based on observed performance of piles which have been load tested over a relatively short period. The question of the effect of time since installation is of much more consequence, particularly for piles installed in sous of low permeability. When piles are driven or formed by boring in soft normaly consolidated and usually sensitive clays high excess pore pressures around the shaft are generated. After the pile is installed, the excess pore pressures dissipate with time. Because of the re-consolidation of the soil around the pile, there is again in the axial capacity after an elapse of time. So the increase obtainable in a soft or sensitive clay can be allowed for design purposes having regard to the time after installation that the pile is required to carry its full design working load. Since the extreme complexities of the problem, there is no simple fundamental method for calculating the ultimate bearing capacity of a pile. The figures, equations and tables given in this study have been proved by experience. Engineer has to decided wheather to base his designs on conservative values with an appropriate safety factors without any check by load testing, or merely to use design methods to give a preliminary guide to pile diameter and length and then to base final designs on an extensive field testing programme with loading tests on failure. Piling practice is rather different from other kinds of engineering in that the finished product is out of sight thus, and enormous trust has to be established between those who designed the pile and those who formed them. Piling should be a compromise from the time a piling solution is considered until the last pile is formed. Practical considerations play an important part in pile design. The role of theorical analysis is then optimize the foundation and to assess, through parametric studies, the effect.of uncertainties in assumed soil and other design parametres. Therefore, piling can be one of the most difficult, operations in civil engineering. Genuine attemts by many engineers in universities and research stations to provide more facts upon which judgements can be based should nat be overlooked.
The Calculation of the pile bearing capacity with statical formulas
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1992
Keywords: Jeoteknik; Kazık taşıma gücü; Geotechnics; Pile bearing capacity